MEQSILHOUETTE: a mm-VLBI observation and signal corruption simulator - Blecher, Tariq (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2017)
The Event Horizon Telescope (EHT) aims to resolve the innermost emission of nearby supermassive black holes, Sgr A* and M87, on event horizon scales. This emission is predicted to be gravitationally lensed by the black hole which should produce a shadow (or silhouette) feature, a precise measurement of which is a test of gravity in the strong-field regime. This emission is also an ideal probe of the innermost accretion and jet-launch physics, offering the new insights into this data-limited observing regime. The EHT will use the technique of Very Long Baseline Interferometry (VLBI) at (sub)millimetre wavelengths, which has a diffraction limited angular resolution of order ~ 10 Âµ-arcsec. However, this technique suffers from unique challenges, including scattering and attenuation in the troposphere and interstellar medium; variable source structure; as well as antenna pointing errors comparable to the size of the primary beam. In this thesis, we present the meqsilhouette software package which is focused towards simulating realistic EHT data. It has the capability to simulate a time-variable source, and includes realistic descriptions of the effects of the troposphere, the interstellar medium as well as primary beams and associated antenna pointing errors. We have demonstrated through several examples simulations that these effects can limit the ability to measure the key science parameters. This simulator can be used to research calibration, parameter estimation and imaging strategies, as well as gain insight into possible systematic uncertainties.
Keywords: Large astronomical telescopes; Very long baseline interferometry; MEQSILHOUETTE (Software); Event horizon telescope